Address at the opening of the thirty-fourth session of the Statistical and Social Inquiry Society of Ireland - Mapother, E. D. (Statistical and Social Inquiry Society of Ireland, 1881)
It can scarcely be hoped that the address you are about to hear will secure approval for the Council in their choice of President, for it will deal with only one of the three branches into which the business of the Society is divided?namely, public health. Even thus restricted, however, my subject needs no apology. Lord Beaconsfield has pronounced public health to be the first care of the statesman, and in Ireland the topic is a pressing one. My address will, however, lack the brilliant illustrations and large philosophical deductions to which you have been accustomed from this chair, and to be practical or suggestive, must needs tax your patience with dry facts and figures, many of them of a sombre character.
Read before the Society, 30 November 1880
Keywords: 314.15